Development of social entrepreneurship in Latvia - Sannikova, Aija; Brante, Inara (Business, Management and Economics Engineering, 2018)
The development of social entrepreneurship as a special business type is in its beginning in Latvia, therefore its development conditions have been researched very little. The legislation regulating this type of business activity commences on the 1st April 2018. In order to promote the development of social entrepreneurship and at the same time promote employment opportunities for unemployed persons who are less favoured, persons with disabilities and other socially vulnerable persons, the EU Structural Funds support for the realization of these strategic goals is available for social businesses. The research carried out a comparative analysis of the legal framework regulating social entrepreneurship in the Baltic States and an analysis of economic preconditions and the support system for social entrepreneurship. The present research contributes to research on social entrepreneurship in two aspects: 1) the legal framework distinguishing this business form from others is analysed; 2) economic preconditions for social entrepreneurship as well as its socio-economic goals and the relevant institutional framework in Latvia are analysed. The subject of the research: preconditions and prerequisites for social entrepreneurship. Methods of the research: the monographic method, statistical analysis and comparative analysis.